Study on the restoration and characteristics of the entrance space of Zuoyin Garden in Huizhou - Min Yan (Cogent Arts & Humanities, 2024)
Zuoyin Garden, built by Huizhou dramatist and publisher Wang Tingne in the late Ming Dynasty, is one of the most representative private gardens in Huizhou, China, and has increasingly attracted scholars’ attention in recent years. Chinese traditional gardens have always focused on the selection, design and organization of the entrance. The entrance space of Zuoyin Garden is different from other gardens in Huizhou, which is the focus of this paper. Based on the analysis of the long scroll print of Huizhou, the Garden View of Huancui Hall and the Notes of Huancui Hall of Mr. Zuoyin, this paper attempts to restore the layout relationship and spatial appearance of the entrance area of Zuoyin Garden, and analyzes its construction characteristics from a streamline and function perspective. The result shows that in the entrance construction of the Zuoyin Garden in late Ming dynasty, some characteristics of Huizhou garden construction are reflected, and the complex and contradictory mentality of the garden owner Wang Tingne is presented. The processing of the entrance space meets the activity requirements of different groups and functions, and reflects the characteristics of excursion, publicness and openness rarely observed in private gardens. This expands the research content of the garden in Huizhou and may be used for reference in contemporary landscape design.